Searching Coordination and Organometallic Compounds in SciFinder. - A. Ben Wagner (Issues in Science and Technology Librarianship)
The primary goal of this article is to assist researchers and librarians to accurately and completely search Chemical Abstracts Service's (CAS) SciFinder web-based system for coordination compounds including organometallics. CAS indexing policies and conventions are described. Appropriate search strategies are explained. Although this article is of primary value for SciFinder researchers, the analysis of how CAS handles this class of compounds will be of use to searchers regardless of the platform used to access Chemical Abstracts information. [ABSTRACT FROM AUTHOR]